Biamperometric Indication with Glassy Carbon-Platinum Electrode System in Non-Aqueous Media Using Iodine-Iodide Couple: Determination of Xanthates and Dithiocarbamates - Ghosh, Debashish; Raghubanshi, Naveen (Asian Journal of Chemistry, 2012)
Glassy carbon-platinum electrode combination has been applied for biamperometric indication in non-aqueous media using iodine-iodide couple for current indication. In the first series of experiments, carried out in acetonitrile medium, potassium alkyl xanthates have been determined using N-bromosuccinimide as the oxidant in the presence of potassium iodide and in the second series metal diethyl dithiocarbamates have been estimated in N,N-dimethylformamide using iodine monobromide. Reverse L-shaped titration curves with well-defined and reproducible breaks leading to precise results have been obtained both for xanthates (3.27-36.04 mg) and diethyl dithiocarbamates (5.07-38.82 mg) with errors not exceeding ± 1 %.